THE SOCIAL ENVIRONMENT IN THE MILITARY FAMILY AND THE DISTRIBUTION OF ROLES IN IT (Intent Research Scientific Journal, 2023)
This article examines the social environment in military families and the distribution of roles within a family unit. It explores the unique challenges faced by military families, their impact on family dynamics, and the strategies used to address these challenges. The study highlights the importance of support systems, effective communication, and adaptive coping mechanisms in fostering stability and well-being in military families.